Study of Palm Seeds (Arenga pinnata Wurmb Merr.) and Its Breaking Dormancy - Farida, Farida; Barunawati, Nunun; Saptadi, Darmawan; Kuswanto, Kuswanto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
Sugar palm (Arenga pinnata) is a versatile Indonesia-native species widely distributed across the archipelago. It can function as a water-conserving plant and provides low-glycemic-index sugar (GI 35.56) from palm sap, allowing safer consumption by people with diabetes. An early-maturing variety, endemic to East Kutai Regency, East Kalimantan Province, has been designated a National Early-Maturing Superior Variety and is promoted as a leading commodity. However, cultivation is constrained by slow seed germination, which may take about two years because of strong seed dormancy. Sugar palm seeds can remain dormant due to morphophysiological, physical, and physiological constraints that inhibit water uptake, embryo growth, and metabolic activation. Previous studies have attempted to accelerate germination using mechanical scarification, chemical treatments, immersion in water at controlled temperatures (stratification), and applications of growth regulators at various concentrations. Reported germination success for scarification ranges from 52.00% to 73.00%, indicating room for improvement. This article reviews and identifies practical approaches to accelerate palm seed germination, emphasizing that effective dormancy-breaking innovations are essential to supply planting material for expanding sugar palm plantations and improving crop production. Such improvements could shorten nursery cycles, enhance seedling uniformity, and strengthen farmer adoption.